Tripod Untuk Kamera Dslr Yang Dikendalikan Oleh Smartphone Android Berbasis Arduino - Habib, Burhan; , Heru Supriyono, S.T M.Sc. Ph.D; , Umi Fadlilah, S.T M.Eng (2016)
On the digital era nowadays, there are lots of automatization implemented on devices that people used in everyday life to help human works, one of them is a tripod. Besides of assisting photographers taking portrait pictures, tripod can be useful of taking pictures that photographers are prohibited of being around (example: spying). For that reason, need to be implemented of automatization on tripod. On this research, automatization done by adding arduino, bluetooth module, and servo motors. Arduino and bluetooth module attached on bottom part of tripod, and the servos attached on head part of the tripod to rotate the camera. With Android smartphone, tripod can be controlled from distance. Application on android smartphone gives byte signal to arduino through bluetooth module, then translated by arduino which then becomes a command to rotate the servo. This tool can be used at a distance of 20 meters which has optimal distance is 10 meters. The accuracy rate of tilting servo is 95,7% and the rotating servo is 99%. Differences in travel time of servo with a load of 850 grams and 1.3 Kg are 0.28 s fot tilting servo, and 0.16 s for rotating servo.